Pengaruh Diversifikasi, Kepercayaan Produk terhadap Penjualan Mobil Hybrid dengan Tren Pasar sebagai Variabel Intervening - Ariya Putra Marwa Pramulya; Yeni Susanti; Hanif Hanif (Jurnal Simki Economic, 2026)
This research analyses the impact of product diversification and product trust on the enhancement of hybrid car sales from an Islamic business perspective. This research employed a quantitative methodology and an explanatory framework. Data was gathered via questionnaires administered to 97 purposively selected consumers of Toyota hybrid vehicles in Bandar Lampung City. Validity, reliability, classical assumption tests, multiple linear regression, and path analysis were conducted on the data for analysis. This is accomplished utilizing statistical software. The research findings indicate that product trust directly impacts and significantly enhances sales, whereas product diversification and market trends exert no partial influence on sales growth. Nevertheless, market developments have failed to mitigate the impacts of product trust and product diversification. The findings underscore the significance of honesty, trust, and transparency in sustainable business operations, indicating that the rise in hybrid car sales is more significantly affected by consumer trust than by product changes or market trends.